Investigating the effect of Mimosa Pudica on dichlorvos induced hippocampal neurodegeneration in mice - Enye Linus Anderson; Saka Olusola Stephen; Onoriode Andrew Udi; Ebeye Abimbola Oladunni; Igbigbi Patrick Sunday (Elsevier, 2023)
Background: Dichlorvos, the Dimethyl Dichlorovinyl Phosphate (DDVP) poisoning is common due to its frequent usage as a food preservative. This is determining to assessing the reversal of DDVP-induced neurodegeneration by Mimosa pudica Methods: Fifty (50) adult BALB/c mice were randomly assigned to five groups (A-E) of 10 mice each. Group A mice were given normal feed and water, Group B mice were treated orally with 400 mg/kg body weight (b.wt.) of Mimosa pudica, Group C mice were fed with 2.5% of 2, 2- DDVP poisoned feed (7ml of DDVP in 300ml of water, sprayed on the feed), Group D mice were fed 2.5% DDVP poisoned feed simultaneously with 400mg/kg b.wt. of Mimosa pudica (MP) orally; and Group E mice were fed 2.5% DDVP poisoned feed for 14 days and then treated orally with 400mg/kg b.wt. of Mimosa pudica for the remaining 14 days. The exposure lasted for 28 days through oral administration. Behavioural studies to assess spatial and non-spatial memory of the mice were carried out on the 27th day using the Y-Maze and Novel Object Recognition (NOR) test. On the 28th the mice were sacrificed using chloroform as anaesthesia. Immunohistochemical studies were perfused transcardially using normal saline followed by perfusion with 10% formal saline.Values were analyzed using Graphpad prism version 5.0. P values was set at 0.05, 0.01 and 0.001. Results: Neurodegeneration was observed in animals exposed to DDVP contaminated feed while treatment with MP after DDVP exposure ameliorated the degeneration taken together. Conclusion: It was concluded that exposure to DDVP contaminated feed induces damage in the hippocampus which leads to synaptic loss and neurodegeneration.